2019
DOI: 10.1038/s41467-019-10051-0
|View full text |Cite
|
Sign up to set email alerts
|

Artisanal fish fences pose broad and unexpected threats to the tropical coastal seascape

Abstract: Gear restrictions are an important management tool in small-scale tropical fisheries, improving sustainability and building resilience to climate change. Yet to identify the management challenges and complete footprint of individual gears, a broader systems approach is required that integrates ecological, economic and social sciences. Here we apply this approach to artisanal fish fences, intensively used across three oceans, to identify a previously underrecognized gear requiring urgent management attention. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 66 publications
0
18
0
Order By: Relevance
“…The levels of juvenile catch recorded for MNF are high and are comparable to other fishing gears that are being used in an unsustainable manner. A recent examination of static fish fence gears found a 40% juvenile fish count (Exton et al 2019), whilst beach seine net gears have been recorded in Kenya to have juvenile proportions at up to 68% (Mangi and Roberts 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of juvenile catch recorded for MNF are high and are comparable to other fishing gears that are being used in an unsustainable manner. A recent examination of static fish fence gears found a 40% juvenile fish count (Exton et al 2019), whilst beach seine net gears have been recorded in Kenya to have juvenile proportions at up to 68% (Mangi and Roberts 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fishing nets, lines, and fences were reported to adversely impact marine fish and coral populations. Exton et al (2019) reported that artisanal fish fences, which funnel fish into a holding structure, cause habitat fragmentation, create physical barriers that interrupt natural movement of mobile species and benthic community structure, and remove large numbers of juvenile fish, which produces a corresponding decline in fish abundance on adjacent coral reefs. Gorgonian coral species in canyon systems of the western Ligurian Sea (northwestern Mediterranean Sea) were found to be negatively impacted by one or more types of derelict fishing gear, with fishing nets causing the greatest impact at most study sites (Giusti et al, 2019).…”
Section: Effects Of Fishing and Aquaculturementioning
confidence: 99%
“…Coral reefs are among the most valuable and vulnerable ecosystems on the planet 1 , 2 . Loss of herbivory, largely driven by disease and the widespread unsustainable harvesting of fish and echinoids in small-scale fisheries 3 , 4 , has many negative impacts on coral reefs, but it is the associated macroalgae overgrowth that poses the greatest threat 5 . In the absence of herbivores, structurally complex, three-dimensional hard corals are replaced by structurally simple two-dimensional macroalgae 6 , 7 , which reduces habitat availability and drives decreases in species richness and abundance 8 .…”
Section: Introductionmentioning
confidence: 99%